Social Media Influence on General Election of India - Mohanty, Shakti Prasad (Digital Repository of Theses, 2026)
There have been multiple cases of unfair social media manipulations to sway the outcome of a democratic election process in today's social media-dominated world. Given that India is the largest democratic nation in the world in terms of the number of voters, this poses significant challenges to the democratic process. Many news stories have talked about how people used social media to change people's minds and affect the result of India's general election. This paper talks about the following main study questions. o Does social media have an impact on the Indian general election? o Are opinions expressed on social media affecting India's general election? Approximately 100,000+ mentions were gathered from social media sites like Instagram, Twitter, and YouTube during different stages of the Indian general election to provide answers to these two research questions. Particular attention was paid to the key hashtags of several well-known political parties, including the BJP, Congress, TMC, and AAP, during the data collection process. Awario.com is a tool for data extraction and analysis. o To determine whether there is a correlation between these data sets and the outcome of the Indian general election, a thorough qualitative and quantitative analysis of these gathered mentions and their characteristics was conducted. o The analysis and outcome, however, failed to find any meaningful correlation between the poll's outcome and the data that was gathered. In fact, it was clear that none of these platforms' social media actions have a big impact on the Indian general election. o Lastly, this study recommends an ongoing procedure to prevent unfair social media manipulations during India's general election